O enigma da "reação espermatofórica": breve síntese do conhecimento sobre a estrutura e o funcionamento dos espermatóforos dos cefalópodes (Mollusca: Cephalopoda) - Marian, José Eduardo Amoroso Rodriguez (Papéis Avulsos de Zoologia, 2011)
Coleoid cephalopods (squids, cuttlefishes, and octopods) produce elaborate spermatophores, which are transferred to the female during mating with the aid of a modified appendage called hectocotylus. During transfer, the spermatophores undergo the so-called spermatophoric reaction, i.e., a complex process of evagination of the ejaculatory apparatus that, ultimately, leads to the extrusion of the cement body and sperm mass. The present review summarizes the bulk of our knowledge on the morphology and functioning of this exclusive coleoid character, identifying gaps and defining strategies to stimulate advancements in this area. Few detailed morphological studies regarding this structure have yet been conducted, and much of the knowledge on the coleoid spermatophore was generated by classical studies of the 19th and early 20th centuries. Furthermore, investigations on the functioning of this structure are even rarer, the basic knowledge of the spermatophoric reaction being restricted to 19 species. There seems to be a consensus in the literature that two types of attachment of spermatophores occur in decapodiforms (i.e., squids and sepioids): superficial attachment, and deep (or intradermal) implantation. In superficial attachment, the base of the spermatangia ends up attached on the surface of the female's body, by means of the adhesive contents and, in some cases, attachment structures of the cement body; this type is found in several groups of decapodiforms (e.g., Loliginidae, Ommastrephidae, Sepiidae). In deep implantation, the spermatangia penetrate autonomously the integument, embedding themselves completely into the female tissue; this strategy is common to some oceanic and deep-sea species (e.g., Architeuthidae, Cranchiidae, Octopoteuthidae, Sepiolidae). The mechanism responsible for deep implantation remains unknown. In octopodiforms (octopods), the spermatophore is inserted inside the lumen of the female gonoduct, reaching the oviducal gland, where the spermathecae are located, or the ovarian cavity. Since the extracorporeal functioning of coleoid spermatophores must rely entirely on the intricate structure and organization of the tunics, membranes, and other structures composing the spermatophore, only detailed investigations of these components would provide the basis for comprehending its mechanics. This paper recommends the development of a specific, efficient protocol for whole-mount staining and permanent preparation of coleoid spermatophores, in order to enable expansion of spermatophore morphological descriptions in taxonomic and anatomical studies, and therefore enhance the knowledge of this unique, still enigmatic structure.